Prevention of unintended pregnancies in Nigeria; the effect of socio-demographic characteristic on the knowledge and use of emergency contraceptives among female university students - Abiodun, Olumide A.; Sotunsa, John; Jagun, Olusoji; Faturoti, Bukola; Ani, Franklin; John, Imaralu; Taiwo, Agboola; Taiwo, Ogechukwu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The proportion of unintended pregnancy remains high in developing regions due to unmet need for contraception and inconsistent use of modern contraceptives. Practice of emergency contraception is particularly important because of the high rates of unintended pregnancy. The aim was to assess the practice of emergency contraception among female students. Methods: A cross-sectional study was conducted among 5,233 female university students in Nigeria. Results: About 25.4% of the students had ever had sex while 64.3% had heard about emergency contraceptives. About half (49.6%) had good knowledge while 70% thought that emergency contraceptives are effective and easy to access and use. Good knowledge about emergency contraceptives was predicted by dwelling urban or suburban areas (AOR=1.750 and 1.817; P<0.05), being single (AOR=2.597, P=0.001), being in the fourth year (AOR=2.096, P<0.001) and having ever had sex (AOR=1.449, P<0.001). Having ever used emergency contraceptive is predicted by good knowledge (AOR=1.852, P<0.001) and perception that emergency contraceptives are effective (AOR=139.774, P<0.001) and easy to access and use (AOR=8.429, P<0.001). Conclusions: Despite a significant risk of unintended pregnancy among female university students, the usage rate of emergency contraceptive is very low. There is a need to actively promote emergency contraception along with other contraceptive methods with the involvement of health workers and the media.